PROGRAM BINA PRIBADI ISLAM (BPI): DAKWAH PONDOK PESANTREN AL-IHSAN RIAU DALAM MEMBANGUN SPIRITUALITAS KOMUNAL - Fajar Illahi (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2026)
This study aims to analyze the role of the Bina Pribadi Islam (BPI) Program as a da'wah medium in fostering community spirituality at Al-Ihsan Islamic Boarding School, Kampar Regency, Riau Province. The research employed a qualitative approach using a case study design within a constructivist paradigm. Data were collected through participant observation, in-depth interviews, and document analysis involving the boarding school principal, BPI coordinator, mentors, community leaders, and program participants selected through purposive sampling. Data were analyzed using the stages of data reduction, data display, and conclusion drawing, while triangulation techniques were employed to ensure the credibility of the findings. The results reveal that the BPI Program effectively strengthens community spirituality through systematic and sustainable activities, including Islamic creed development (aqidah), habituation of worship practices, mentoring, muhasabah (self-reflection), and exemplary guidance provided by mentors. The program not only enhances participants' religious understanding and quality of worship but also cultivates religious character, discipline, self-control, social responsibility, and strengthens Islamic brotherhood (ukhuwah Islamiyah). Furthermore, the spiritual transformation experienced by participants contributes to greater community involvement in religious and social activities, thereby reinforcing social solidarity and harmonious social relations. Nevertheless, sustaining these positive outcomes requires continuous post-program mentoring to preserve the internalized Islamic values. This study concludes that the BPI Program represents an effective pesantren-based transformative da'wah model for addressing the spiritual challenges of contemporary society while reinforcing the role of Islamic boarding schools as agents of social transformation. Keywords: Bina Pribadi Islam; Transformative Da'wah; Community Spirituality.[Penelitian ini bertujuan menganalisis peran Program Bina Pribadi Islam (BPI) sebagai media dakwah dalam membangun spiritualitas masyarakat di Pondok Pesantren Al-Ihsan Riau, Kabupaten Kampar. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus dan paradigma konstruktivis. Data diperoleh melalui observasi partisipatif, wawancara mendalam, dan dokumentasi terhadap pimpinan pesantren, koordinator BPI, pembina, tokoh masyarakat, serta peserta program yang dipilih secara purposive. Analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan dengan teknik triangulasi untuk menjamin keabsahan temuan. Hasil penelitian menunjukkan bahwa Program BPI mampu membangun spiritualitas masyarakat melalui pembinaan akidah, pembiasaan ibadah, mentoring, muhasabah, dan keteladanan pembina yang dilaksanakan secara sistematis dan berkelanjutan. Program ini tidak hanya meningkatkan pemahaman keagamaan dan kualitas ibadah peserta, tetapi juga membentuk karakter religius, kedisiplinan, pengendalian diri, kepedulian sosial, serta memperkuat ukhuwah Islamiyah. Perubahan spiritual yang terjadi turut berdampak pada meningkatnya partisipasi masyarakat dalam aktivitas keagamaan dan sosial, sehingga memperkuat solidaritas dan kehidupan sosial yang harmonis. Meskipun demikian, keberlanjutan hasil pembinaan masih memerlukan pendampingan pascaprogram agar nilai-nilai yang telah diinternalisasikan tetap terpelihara. Penelitian ini menegaskan bahwa Program BPI merupakan model dakwah transformatif berbasis pesantren yang efektif dalam menjawab tantangan krisis spiritual masyarakat kontemporer sekaligus memperkuat fungsi pesantren sebagai agen perubahan sosial].Keywords: Bina Pribadi Islam; Dakwah Transformatif; Spiritualitas Masyarakat.